Variability in quantitative parameters of instrumental swallowing assessments: a scoping review protocol - Bandeira,Jayne de Freitas (2022)
ABSTRACT Purpose: to present a scoping review protocol mapping scientific evidence on the level of variability in quantitative parameters or outcomes extracted with instrumental swallowing examinations. Methods: a protocol following the methodological approach designed by the Joanna Briggs Institute and the scoping review recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols - extension for scoping reviews (PRISMA-ScR). The search will be made in PubMed/MEDLINE, LILACS, Cochrane Library, EMBASE, Web of Science, Scopus, and CINAHL and the grey literature (Google Scholar and ProQuest) with a search strategy developed for PubMed/MEDLINE, adapted for each database. Two independent reviewers will initially select articles by title and abstract, and the full text of the selected ones will be read and analyzed according to the eligibility criteria. Data will be extracted from the selected articles in a standardized form, and the results will be presented in a flowchart and narrative summary, following PRISMA-ScR guidelines. Final considerations: the scoping review resulting from this protocol is expected to present the overall state of the scientific evidence and identify gaps in the topic that need to be addressed in studies.